Senggayung Music in Gerai Village, Ketapang Regency: The Study of The Form and Cultural Identity - Harriska, Harriska; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2018)
Senggayung music classified as an idiophone musical instrument that is made of bamboo. Senggayung music only exist in Ketapang District, unique music that is not owned by other regions. This study aims to analyze the form of Senggayung music and identify the cultural identity of the Gerai Village community through Senggayung music. The approach used is an interdisciplinary approach involving ethnomusicology and anthropology disciplines. Technique of collecting data with observation, interview, and study of documentation. Data validity techniques use credibility with data triangulation techniques. Data analysis by means of data collection, data reduction, data presentation, and verification or withdrawal of conclusions. The results of this study show, When viewed from the organology, Senggayung belong to idiophone musical instruments made of bamboo. Senggayung is a music that reflects the cultural identity of the village community of Ketapang regency. Senggayung used in the process of community ceremony, before starting the elders read the Spells to raoh ancestors participate in the ceremony process. Senggayung taught to the young generation by the elders for Senggayung remain sustainable and not extinct. Some of the factors that make up the cultural identity are (1) belief, (2) language, (3) behavior pattern which is reflected in Senggayung is a cultural identity.